Preparation method of negative-electrode-free solid-state lithium battery based on double-salt polymer solid-state electrolyte

By adopting dual-salt polymer solid electrolyte and negative electrode-free design in lithium-ion batteries, the problems of low energy density and safety risks of traditional lithium-ion batteries are solved, and a negative electrode-free solid lithium battery with high energy density, long life and high safety is achieved.

CN119890466APending Publication Date: 2025-04-25DALIAN UNIV OF TECH

Patent Information

Application Number
CN202510074948.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have low energy density and safety risks, making it difficult to meet the needs of high energy consumption, long battery life and high safety.

Method used

A negative electrode solid state lithium battery preparation method based on double salt polymer solid electrolyte is adopted to prepare a high-stability polymer solid state electrolyte by heat-induced radical polymerization reaction of acrylate, and match it with existing lithium-ion battery positive electrode materials and metal current collectors to achieve high energy, long life and high safety negative electrode solid state lithium battery.

Benefits of technology

The energy density is higher than 310Wh/kg, the cycle life is up to 330 times, and there is no smoke or fire under mechanical puncture conditions, which significantly improves the safety and practical application potential of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890466A_ABST
    Figure CN119890466A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a negative-electrode-free solid-state lithium battery based on a double-salt polymer solid-state electrolyte, and belongs to the technical field of new energy. The method comprises the following steps: dissolving a bi-component lithium salt, adding a polymer monomer, and stirring to obtain a solid electrolyte precursor solution; secondly, adding a polymerization initiator into the precursor solution, and obtaining a solid electrolyte under a heating condition; and finally, adding the solid electrolyte between the positive electrode of the lithium ion battery and the metal current collector to prepare the negative-electrode-free solid-state lithium battery. The high-stability polymer solid electrolyte with an electrochemical stability window as high as 5.5 V is prepared by utilizing a thermal-initiated free radical polymerization reaction of acrylate, the polymer solid electrolyte is matched with an existing lithium ion battery positive electrode material and a metal current collector, and under the condition that a negative electrode active material is not used, the high-stability polymer solid electrolyte is prepared. The negative-electrode-free solid-state lithium battery with high energy, long service life and high safety is realized; the mass specific energy of the negative-electrode-free solid-state lithium battery is greater than 310 Wh kg <-1 >, the cycle life is 310 times, and the negative-electrode-free solid-state lithium battery has excellent safety under a mechanical puncture condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new energy technology and relates to a method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte. Background Art

[0002] High-performance battery technology is a major demand for my country's transformation and upgrading from fossil energy to renewable energy structure and the development of a low-carbon clean economy. However, the energy density of traditional lithium-ion batteries can no longer meet the needs of high-energy consumption and long-range mobile electrification applications. In addition, as the number of new energy vehicles rapidly increases from millions to tens of millions, the requirements for battery safety are increasingly becoming the focus of competition between the new energy industry and the development of a low-carbon economy. Traditional lithium-ion batteries use flammable and leaky organic electrolytes, face serious safety risks, and are difficult to meet this demand.

[0003] In traditional lithium-ion batteries, the graphite anode accounts for more than 25-40% of the battery weight and thickness, which restricts the battery's unit mass and unit volume energy density. Using a high-capacity metal lithium anode can significantly improve the battery's energy density. However, the thickness of commercial metal lithium foil is usually more than hundreds of microns, resulting in a waste of battery energy efficiency and lithium resource costs. To solve this problem, ultra-thin metal lithium foil is needed, but the manufacturing cost of ultra-thin metal lithium foil is high and difficult to use in practice.

[0004] A negative electrode-free battery is a new type of battery system consisting of a positive electrode material and a metal current collector on the negative electrode side. The negative electrode side does not contain metallic lithium in the initial state. During the first charge, the lithium ions released by the positive electrode are deposited on the surface of the current collector on the negative electrode side in the form of metallic lithium. Because there is no excess negative electrode active material inside the battery, the volume energy density and mass energy density of the battery can be greatly improved. At the same time, the battery manufacturing process does not require water and oxygen-sensitive lithium metal, and has good compatibility with existing lithium-ion battery production lines. However, due to irreversible lithium loss and metallic lithium dendrite growth inside the battery, negative electrode-free batteries face problems such as low coulomb efficiency and short cycle life. The use of flammable organic liquid electrolytes also reduces their safety, seriously restricting the practical application of such new batteries. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte. The present invention utilizes the thermally initiated free radical polymerization reaction of acrylate to prepare a high-stability polymer solid electrolyte with an electrochemical stability window of up to 5.5V, and matches the polymer solid electrolyte with the existing lithium-ion battery positive electrode material and metal current collector to achieve a high-energy, long-life, high-safety negative electrode-free solid-state lithium battery without using negative electrode active materials. The present invention can avoid the use of highly active, water-oxygen-sensitive, and expensive ultra-thin lithium foil as the negative electrode, and avoids the use of flammable liquid electrolytes, solving the problems of low energy density and safety risks of traditional lithium-ion batteries.

[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte, the negative electrode-free solid-state lithium battery preparation method comprising the following steps:

[0008] In the first step, a two-component lithium salt is dissolved in an organic solvent and a polymer monomer is added, followed by thorough stirring to obtain a solid electrolyte precursor solution.

[0009] In the second step, after adding a polymerization initiator to the solid electrolyte precursor solution, a free radical polymerization reaction is initiated under heating conditions to obtain a double salt polymer solid electrolyte.

[0010] The third step is to prepare the positive electrode of the lithium-ion battery.

[0011] The fourth step is to add the double salt polymer solid electrolyte obtained in the second step between the positive electrode of the lithium ion battery and the metal current collector to prepare a negative electrode-free solid-state lithium battery.

[0012] Furthermore, in the first step, the organic solvent is at least one of diethyl carbonate, ethylene carbonate, and propylene carbonate; the lithium salt is at least two of lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, and lithium tetrafluoroborate; and the polymer is at least one of polyethylene glycol diacrylate and polydipentaerythritol pentaacrylate.

[0013] Furthermore, in the first step, the concentration of the lithium salt in the solid electrolyte precursor solution is 100 to 400 mg / mL -1 ; The mass of the polymer accounts for 5 to 50% of the total weight of the solid electrolyte precursor solution; the stirring speed is 400 to 800 rpm, and the stirring time is 4 to 8 hours.

[0014] Further, in the second step, the polymerization initiator is azobisisobutyronitrile, and the concentration is 1 to 10 mg mL -1, the heating temperature is 60-80°C, and the polymerization time is 2-10h.

[0015] Furthermore, in the third step, the lithium-ion battery positive electrode is prepared by using a lithium-ion battery positive electrode material, a conductive agent and a binder. Specifically, the lithium-ion battery positive electrode material, the conductive agent and the binder are uniformly mixed in a mass ratio of 8:1:1, N-methylpyrrolidone is added as a solvent and a dispersant, and the resulting slurry is uniformly coated on a copper foil to obtain a lithium-ion battery positive electrode.

[0016] Furthermore, the positive electrode material of the lithium-ion battery is at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium sulfide, and lithium nickel cobalt manganese oxide; the conductive agent is at least one of carbon black, carbon nanotubes, and graphene; and the binder is polyvinylidene fluoride.

[0017] Furthermore, in the fourth step, the metal current collector is one of copper and stainless steel foil / mesh coated with a carbon layer on the surface.

[0018] Furthermore, in the fourth step, a solid electrolyte precursor solution is added between the positive electrode of the lithium-ion battery and the metal current collector, a polymerization initiator is added according to step 2), the battery is packaged, and the battery is allowed to stand under heating conditions to obtain a negative electrode-free solid-state lithium battery. The heating temperature is 60 to 80° C., and the standing time is 2 to 10 hours.

[0019] Compared with the prior art, the beneficial effects are:

[0020] (1) Since no negative electrode material is used, the energy density of the new negative electrode-free solid-state lithium battery constructed by the present invention is >310Whkg -1 , higher than traditional liquid lithium-ion batteries, and does not emit smoke or fire under mechanical puncture conditions.

[0021] (2) The use of polymer solid electrolytes instead of flammable and leaky liquid electrolytes solves the problem of leakage of organic flammable electrolytes during battery use.

[0022] (3) The prepared dual salt polymer solid electrolyte can improve the reversibility of lithium deposition / stripping by inducing the formation of an organic-inorganic composite positive and negative electrode interface film rich in inorganic components, thereby extending the cycle life of the negative electrode-free lithium battery to 330 times.

[0023] (4) The negative electrode-free solid-state lithium battery preparation process can be directly applied to the existing lithium-ion battery production process and is suitable for large-scale manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the infrared spectrum of the polymer solid electrolyte prepared in Example 1 of the present invention;

[0025] Figure 2It is an electrochemical stability window test of the polymer solid electrolyte prepared in Example 1 of the present invention;

[0026] Figure 3 is the cycle life of the negative electrode-free solid-state lithium battery prepared in Example 1 of the present invention;

[0027] Figure 4 This is a safety test of the negative electrode-free solid-state lithium battery prepared in Example 1 of the present invention under mechanical puncture. DETAILED DESCRIPTION

[0028] In view of the many defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle, etc. will be further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described in the following (embodiments) can be combined with each other to form a new or preferred technical solution.

[0029] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0030] Example 1

[0031] 1) Add lithium difluorooxalate borate and lithium bis(fluorosulfonyl)imide to diethyl carbonate and propylene carbonate, and add polyethylene glycol diacrylate, and stir well to obtain a solid electrolyte precursor solution. The concentrations of lithium difluorooxalate borate and lithium bis(fluorosulfonyl)imide are both 200 mg mL -1 , the ratio of the two lithium salts is 1:1; the content of the polymer is 30%; the stirring speed is 600 rpm, and the stirring time is 6 hours.

[0032] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) to initiate a free radical polymerization reaction under heating conditions to obtain a double salt polymer solid electrolyte. The polymerization initiator is azobisisobutyronitrile with a concentration of 5 mg mL -1 , the heating temperature is 60℃ and the polymerization time is 5h.

[0033] 3) The positive electrode material of lithium nickel cobalt manganese oxide, the graphene conductive agent and the polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was added as a solvent and dispersant, and the obtained slurry was uniformly coated on the carbon-coated copper foil as the positive electrode. The positive electrode material loading was 5 mg cm -2 ; The conductive agent is polyvinylidene fluoride.

[0034] 4) Add the solid electrolyte precursor solution obtained in step 1) between the positive electrode of the lithium ion battery obtained in step 3) and the metal current collector, add a polymerization initiator according to step 2), encapsulate the battery, and stand under heating conditions to obtain a negative electrode-free solid lithium battery. The metal current collector is a copper foil coated with a carbon layer. The heating temperature is 60°C and the standing time is 5 hours.

[0035] The electrochemical stability window of the dual salt polymer solid electrolyte prepared in this embodiment exceeds 5.5V, and the mass specific energy of the negative electrode-free solid lithium battery is greater than 310Wh kg -1 , cycle life of 330 times, and no smoke or fire under mechanical puncture conditions.

[0036] Example 2

[0037] 1) Add lithium difluorooxalatoborate and lithium bis(fluorosulfonyl)imide to diethyl carbonate and propylene carbonate, and add polyethylene glycol diacrylate, and stir well to obtain a solid electrolyte precursor solution. The concentration of lithium difluorooxalatoborate is 50 mg mL -1 , the concentration of lithium bis(fluorosulfonyl)imide is 250 mg mL -1 , the ratio of the two lithium salts is 1:5; the content of the polymer is 20%; the stirring speed is 400 rpm, and the stirring time is 8 hours.

[0038] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) to initiate a free radical polymerization reaction under heating conditions to obtain a double salt polymer solid electrolyte. The polymerization initiator is azobisisobutyronitrile with a concentration of 10 mg mL -1 , the heating temperature is 60℃ and the polymerization time is 5h.

[0039] 3) The positive electrode material of lithium nickel cobalt manganese oxide, the graphene conductive agent and the polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was added as a solvent and dispersant, and the obtained slurry was uniformly coated on the carbon-coated copper foil as the positive electrode. The positive electrode material loading was 5 mg cm -2 ; The conductive agent is polyvinylidene fluoride.

[0040] 4) Add the solid electrolyte precursor solution obtained in step 1) between the positive electrode of the lithium ion battery obtained in step 3) and the metal current collector, add a polymerization initiator according to step 2), encapsulate the battery, and stand under heating conditions to obtain a negative electrode-free solid lithium battery. The metal current collector is a copper foil coated with a carbon layer. The heating temperature is 60°C and the standing time is 5 hours.

[0041] Example 3

[0042] 1) Add lithium difluorooxalate borate and lithium bis(trifluoromethylsulfonyl imide) to diethyl carbonate and propylene carbonate, and add polyethylene glycol diacrylate, and stir well to obtain a solid electrolyte precursor solution. The concentrations of lithium difluorooxalate borate and lithium bis(trifluoromethylsulfonyl imide are both 200 mg mL -1 , the ratio of the two lithium salts is 1:1; the content of the polymer is 35%; the stirring speed is 800 rpm, and the stirring time is 4 hours.

[0043] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) to initiate a free radical polymerization reaction under heating conditions to obtain a double salt polymer solid electrolyte. The polymerization initiator is azobisisobutyronitrile with a concentration of 5 mg mL -1 , the heating temperature is 60℃ and the polymerization time is 5h.

[0044] 3) The lithium iron phosphate positive electrode material, carbon black conductive agent and polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was added as a solvent and dispersant, and the resulting slurry was uniformly coated on the carbon-coated copper foil as the positive electrode. The positive electrode material loading was 5 mg cm -2 ; The conductive agent is polyvinylidene fluoride.

[0045] 4) Add the solid electrolyte precursor solution obtained in step 1) between the positive electrode of the lithium ion battery obtained in step 3) and the metal current collector, add a polymerization initiator according to step 2), encapsulate the battery, and stand under heating conditions to obtain a negative electrode-free solid lithium battery. The metal current collector is a copper foil coated with a carbon layer. The heating temperature is 60°C and the standing time is 5 hours.

[0046] Example 4

[0047] 1) Add lithium difluorooxalate borate and lithium hexafluorophosphate to diethyl carbonate and propylene carbonate, and add polydipentaerythritol pentaacrylate, and stir well to obtain a solid electrolyte precursor solution. The concentration of lithium difluorooxalate borate is 100 mg mL -1 , the concentration of lithium hexafluorophosphate is 400 mg mL -1 , the ratio of the two lithium salts is 1:4; the content of the polymer is 50%; the stirring speed is 600 rpm, and the stirring time is 6 hours.

[0048] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) to initiate a free radical polymerization reaction under heating conditions to obtain a double salt polymer solid electrolyte. The polymerization initiator is azobisisobutyronitrile with a concentration of 5 mg mL -1 , the heating temperature is 70℃ and the polymerization time is 8h.

[0049] 3) The lithium manganese iron phosphate positive electrode material, carbon nanotube conductive agent and polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 8:1:1, N-methylpyrrolidone was added as a solvent and dispersant, and the resulting slurry was uniformly coated on the carbon-coated copper foil as the positive electrode. The positive electrode material loading was 5 mg cm -2 ; The conductive agent is polyvinylidene fluoride.

[0050] 4) Add the solid electrolyte precursor solution obtained in step 1) between the positive electrode of the lithium ion battery obtained in step 3) and the metal current collector, add a polymerization initiator according to step 2), encapsulate the battery, and stand under heating conditions to obtain a negative electrode-free solid lithium battery. The metal current collector is a copper foil coated with a carbon layer. The heating temperature is 70°C and the standing time is 8 hours.

[0051] The above-described embodiments merely express the implementation methods of the present invention, but they should not be understood as limiting the scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte, characterized in that: The method for preparing a negative electrode-free solid-state lithium battery comprises the following steps: In the first step, a two-component lithium salt is dissolved in an organic solvent and a polymer monomer is added, and the mixture is stirred thoroughly to obtain a solid electrolyte precursor solution; The second step is to add a polymerization initiator to the solid electrolyte precursor solution, and initiate a free radical polymerization reaction under heating conditions to obtain a double salt polymer solid electrolyte; The third step is to prepare the positive electrode of the lithium-ion battery; The fourth step is to add the double salt polymer solid electrolyte obtained in the second step between the positive electrode of the lithium ion battery and the metal current collector to prepare a negative electrode-free solid-state lithium battery.

2. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 1, characterized in that: In the first step, the organic solvent is at least one of diethyl carbonate, ethylene carbonate, and propylene carbonate; the lithium salt is at least two of lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, and lithium tetrafluoroborate; and the polymer is at least one of polyethylene glycol diacrylate and polydipentaerythritol pentaacrylate.

3. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 1, characterized in that: In the first step, the solid electrolyte precursor solution has a lithium salt concentration of 100 to 400 mg / mL. -1 ; The mass of the polymer accounts for 5 to 50% of the total weight of the solid electrolyte precursor solution; the stirring speed is 400 to 800 rpm, and the stirring time is 4 to 8 hours.

4. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 1, characterized in that: In the second step, the polymerization initiator is azobisisobutyronitrile with a concentration of 1 to 10 mg mL -1 ; The heating temperature is 60-80°C and the polymerization time is 2-10h.

5. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 1, characterized in that: In the third step, the lithium-ion battery positive electrode is prepared by using lithium-ion battery positive electrode material, a conductive agent and a binder.

6. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 5, characterized in that: The positive electrode material of the lithium-ion battery, the conductive agent and the binder are uniformly mixed in a mass ratio of 8:1:1, N-methylpyrrolidone is added as a solvent and a dispersant, and the obtained slurry is uniformly coated on a copper foil to obtain a positive electrode of the lithium-ion battery.

7. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 5, characterized in that: The positive electrode material of the lithium-ion battery is at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium sulfide, and lithium nickel cobalt manganese oxide; the conductive agent is at least one of carbon black, carbon nanotubes, and graphene; and the binder is polyvinylidene fluoride.

8. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 1, characterized in that: In the fourth step, the metal current collector is one of copper and stainless steel foil / mesh coated with a carbon layer on the surface.

9. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 5, characterized in that: In the fourth step, a solid electrolyte precursor solution is added between the positive electrode of the lithium-ion battery and the metal current collector, a polymerization initiator is added according to step 2), the battery is packaged, and allowed to stand under heating conditions to obtain a negative electrode-free solid-state lithium battery.

10. The method for preparing a negative electrode-free solid-state lithium battery based on a double salt polymer solid electrolyte according to claim 9, characterized in that: The heating temperature is 60-80° C., and the standing time is 2-10 hours.

Citation Information

Patent Citations

  • High-load lithium-rich positive electrode based on MXene and micron lithium sulfide and application of high-load lithium-rich positive electrode in quasi-solid-state negative-electrode-free lithium battery

    CN114203953A

  • Cylindrical anodeless solid state battery with quasi-solid state lithium gel layer

    CN114207929A

  • In-situ polymerization gel polymer electrolyte for improving interface stability, preparation and application

    CN115799624A

  • Flame-resistant quasi-solid hybrid electrolyte for safe anode-less lithium batteries and production method

    US20220077490A1

  • Flame-resistant quasi-solid and solid-state electrolytes, lithium batteries and manufacturing method

    US20220238914A1

Cited By

  • Flame-retardant double-salt polymer solid electrolyte as well as preparation method and application thereof

    CN120376736A

  • Ultrahigh-energy-density solid-state lithium metal battery and preparation method thereof

    CN121618064A

  • An ultrahigh energy density solid-state lithium metal battery and a preparation method thereof

    CN121618064B